Lakshadweep Development Report - Planning Commission (Planning Commission, 2007)
The social and economic development of small islands is beset with a set of challenges that are quite unique. The idyllic geography and climate of such islands have made many of these islands haven of tourism, some of the examples being the Seychelles, Mauritius, Fiji, Papua New Guinea, Maldives, Andamans, Lakshadweep and Singapore. However, these regions face serious threats as well from various sources. Their fragile ecology does not go smoothly with large influx of visitors.
Planning Commission Government of India
Planning Commission Government of India